RSM, ANN-GA and ANN-PSO modeling of SDBS removal from greywater in rural areas via Fe2O3-coated volcanic rocks - Feng, Xiaoying; Liu, Yuankun; Li, Xing; Liu, Hongrun (RSC advances, 2022)
Decontamination and reuse of greywater in rural areas has attracted increasing attention. Typical contaminants in grey water are SDBS, which has a stubborn molecular structure. In this study, Fe2O3-coated volcanic rocks (Fe2O3-VR) prepared from FeCl3 solution by a heating evaporation method can reach 95% removal of SDBS, which is 80% higher than before. The effect of contact time, pH, initial concentration, FeCl3 solution concentration, adsorbent dosage and calcination temperature on the removal rate was researched and modeled by response methodology (RSM) and artificial neural network (ANN). Based on the univariate test, the Box-Behnken design method was used to establish the data sample, which represented a quadratic polynomial model with p-value <0.001, R2 = 0.9872, while the ANN model has the better performance with R2 = 0.9961. The weights of the BP-ANN model were further analyzed using the Garson equation, and the results showed that the validity ranking of the variables was as follows: contact time (37.31%) > calcination temperature (29.43%) > dosage (24.44%) > initial concentration (17.18%) > FeCl3 solution concentration (17.18%) > pH (11.56%). Genetic algorithm (GA) and particle swarm optimization (PSO) were selected to optimize the process parameters. The results showed that ANN-PSO methodology presented a satisfactory alternative and the predicted removal efficiency was 99.9982% with relative error = 0.2230. The optimum level of contact time, pH, initial SDBS concentration, FeCl3 solution concentration, adsorbent dosage and calcination temperature is 136.45 min, 5.64, 22.4 mg L−1, 0.3 mol L−1, 83.21 g L−1, 274.02 °C, respectively. Moreover, Fe2O3-VR was characterized via instrumental analyses (SEM-EDS, FTIR, XRD, BET).